PENGARUH KARAKTERISTIK INDIVIDU PADA ETIKA PENYUSUN LAPORAN KEUANGAN SATUAN KERJA PERANGKAT DAERAH KABUPATEN JEMBRANA - Krisna Astuti, Ida ayu kade; Putra Astika, Ida Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
800x600 This study aimed is to obtain empirical evidence about the influence of individual characteristic (locus of control, work experience, equity sensitivity , gender, and major in college) on the financial report arranging ethic of SKPD of the local government of Jembrana. The samples used in this study were 87 financial report arranging , covering 38 PPK SKPD and 49 treasurer . The sample was taken by using purposive sampling tecnique , which is the person of accounting function in local goverment of Jembrana. This study is examined by multiple linear regression. The instruments has been examined for its validity and reliability and t he model has passed the classical assumptions. The test results shows that the variables of locus of control, work experience, equity sensitivity affects the financial report arranging ethic, while gender, and major in college did not affects the financial report arranging ethic. Normal 0 false false false IN X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif";}
Keywords: Locus of Control, Work Experience, Equity Sensitivity , Gender, Major in College, the financial report arranging ethic.